2020
DOI: 10.1029/2020gl090021
|View full text |Cite
|
Sign up to set email alerts
|

Ganymede‐Induced Decametric Radio Emission: In Situ Observations and Measurements by Juno

Abstract: At Jupiter, part of the auroral radio emissions are induced by the Galilean moons Io, Europa, and Ganymede. Until now, they have been remotely detected, using ground-based radio telescopes or electric antennas aboard spacecraft. The polar trajectory of the Juno orbiter allows the spacecraft to cross the magnetic flux tubes connected to these moons, or their tail, and gives a direct measure of the characteristics of these decametric moon-induced radio emissions. In this study, we focus on the detection of a rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 39 publications
3
40
1
Order By: Relevance
“…in which α is the emission angle, v is the speed of the energetic electrons, c is the speed of light, f ce is the electron's cyclotron frequency, and f ce,max is the maximum cyclotron frequency that the electrons can reach along the active field line from which the DAM is emitted. This formula is based on the loss-cone distribution of electrons, which has been supported by Juno in situ observations (Louarn et al, 2017(Louarn et al, , 2018Louis et al, 2020). Another constraint in the method is the hemisphere from which the DAM emits.…”
Section: Updated Results Of the Io-dam On 2014 March 14mentioning
confidence: 96%
“…in which α is the emission angle, v is the speed of the energetic electrons, c is the speed of light, f ce is the electron's cyclotron frequency, and f ce,max is the maximum cyclotron frequency that the electrons can reach along the active field line from which the DAM is emitted. This formula is based on the loss-cone distribution of electrons, which has been supported by Juno in situ observations (Louarn et al, 2017(Louarn et al, , 2018Louis et al, 2020). Another constraint in the method is the hemisphere from which the DAM emits.…”
Section: Updated Results Of the Io-dam On 2014 March 14mentioning
confidence: 96%
“…At higher frequencies (see Figure S3 in Supporting Information S1), Waves measured strong intensification at frequencies near the local electron cyclotron frequency f ce around the time of crossing, suggesting Juno may have flown through or near the radio source. From several radio source crossings recorded by Juno, the cyclotron maser instability (CMI) driven by a loss-cone distribution function has been established as a major process at Jupiter to generate hectometric and decametric emissions, induced or not by the Galilean moons (Louarn et al, 2017(Louarn et al, , 2018Louis et al, 2020). Following these studies and assuming a loss-cone-driven CMI emission in a weakly relativistic case, the electron energy can be estimated.…”
Section: Description Of the Eventmentioning
confidence: 99%
“…Unlike most Io crossings, measurements connected to the Europa footprint tail showed signs of an electron distribution resulting at least in part from electrostatic acceleration processes, with enhanced precipitating electrons in the 0.38-25 keV range . Evidence for Alfvénic acceleration was observed during a Ganymede tail crossing (Szalay et al, 2020a), showing (a) broadband electrons with precipitating fluxes of ∼11 mW/m 2 and enhanced flux in the 0.5-40 keV range, (b) a strong magnetic Alfvénic perturbation with associated Poynting flux of ∼100 mW/m 2 , that is, ∼10 times the precipitating electron energy flux (EF) measured by Juno's in situ instruments, and (c) strong associated decametric emissions (Louis et al, 2020).…”
mentioning
confidence: 99%
“…2, right panel). When Juno crosses an M-shell that intersects the orbit of one of Jupiter's moons, variations in the charged particle environment (Szalay et al, 2020), plasma waves (Sulaiman et al, 2020), radio emissions (Louis et al, 2020), and magnetic field (Gershman et al, 2019;Connerney et al, 2020;Allegrini et al, 2020) are observed associated with the moon's interaction with the Jovian magnetosphere. Juno's 11th orbit presented a particularly auspicious opportunity to observe Ganymede's interaction with the magnetosphere, with numerous traversals of Ganymede's M-shell occurring at small phase angle separation.…”
Section: Observationsmentioning
confidence: 99%